2006
DOI: 10.2754/avb200675020197
|View full text |Cite
|
Sign up to set email alerts
|

Histological Study of the First Seven Days of Skin Wound Healing in Rats

Abstract: Vidinsk˘ B., P. Gal, T. Toporcer, F. Longauer, L. Lenhardt, N. Bobrov, J. Sabo: Histological Study of the First Seven Days of Skin Wound Healing in Rats. Acta Vet. Brno 2006, 75: 197-202.The aim of this study was to elaborate a histological model of incisional skin wound healing in Sprague-Dawley rats. Under aseptic conditions two paravertebral full thickness skin incisions were performed on the back of 42 anesthetized male rats. Histological sections from tissue specimens were stained by hematoxylin and eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 13 publications
0
28
0
2
Order By: Relevance
“…Hence, the use of a standardized and reproducible model is inevitable to obtain objective information of the wound healing process as well as to better understand the pathological process and to improve medical technologies (Motlik et al, 2007). When compared with our previous histological study, in which we have elaborated a detailed biomechanical and histological model of primary sutured wound healing Vidinsky et al, 2006), our current work shows that there are only quantitative differences between primary and secondary wound healing. This observation was previously shown by numerous authors (Barbul and Regan, 1993;Cotran et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…Hence, the use of a standardized and reproducible model is inevitable to obtain objective information of the wound healing process as well as to better understand the pathological process and to improve medical technologies (Motlik et al, 2007). When compared with our previous histological study, in which we have elaborated a detailed biomechanical and histological model of primary sutured wound healing Vidinsky et al, 2006), our current work shows that there are only quantitative differences between primary and secondary wound healing. This observation was previously shown by numerous authors (Barbul and Regan, 1993;Cotran et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…Whereas an open wound heals with extensive granulation tissue production, a primary wound forms no or only a negligible amount of granulation tissue. 20,30 Therefore, it may be suggested that optimal LLLT probably will be wound-type specific.…”
Section: Discussionmentioning
confidence: 99%
“…Keterangan: do = diameter luka awal; dn = diameter luka pada hari pengamatan Diameter didapat dari rata-rata dua area luka punggung kanan dan kiri (Vidinskỳ et al, 2006) dengan mengukur 4 sisi diameter luka dengan jangka sorong (Morton and Malone, 1972) dan dari. Pengukuran diameter luka dilakukan pada sore hari.…”
Section: Persentase Penutupan Luka (Pl%)unclassified